"The Journey I Have Been Through": The Role of Religion and Spirituality in Aging Well Among HIV-Positive Older Adults. (March 2018) - Emlet, Charles A.; Harris, Lesley; Pierpaoli, Christina M.; Furlotte, Charles
The National Institutes of Health human immunodeficiency virus (HIV) and Aging Working Group identified spirituality as a research emphasis. This qualitative study examines the importance of religion and spirituality among 30 HIV-positive older adults. Using modified grounded theory, adults 50+ were recruited in Ontario, Canada, through AIDS service organizations, clinics, and community agencies. Descriptions of religion and spirituality encapsulated the idea of a journey, which had two components: the long-term HIV survivor profile combined with the experience of aging itself. A final category of HIV as a spiritual journey was finalized through consensus and included the properties of (1) being rejected by as well as rejection of formalized religion, (2) differentiating spirituality from religion, (3) having a connection, (4) feeling grateful, and (5) mindfulness and learning new skills. Interventions fostering resilience and strengths in HIV-positive older adults using spirituality should be considered, including the promotion of person-centered spirituality and interventions that include mindfulness and skill building.